2007
DOI: 10.1126/science.1147417
|View full text |Cite
|
Sign up to set email alerts
|

A Melanocortin 1 Receptor Allele Suggests Varying Pigmentation Among Neanderthals

Abstract: The melanocortin 1 receptor (MC1R) regulates pigmentation in humans and other vertebrates. Variants of MC1R with reduced function are associated with pale skin color and red hair in humans of primarily European origin. We amplified and sequenced a fragment of the MC1R gene (mc1r) from two Neanderthal remains. Both specimens have a mutation that was not found in approximately 3700 modern humans analyzed. Functional analyses show that this variant reduces MC1R activity to a level that alters hair and/or skin pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 266 publications
(162 citation statements)
references
References 27 publications
6
147
0
6
Order By: Relevance
“…Dentine powder samples (usually <100 mg) and some bone samples were extracted as described (15), and mtDNA was amplified using a two-step PCR protocol (12). In each PCR, one or two blocking primers, designed to anneal to the anatomically modern contaminant sequences (Cambridge Reference Sequence haplotype) and prevent their amplification (27), were added.…”
Section: Methodsmentioning
confidence: 99%
“…Dentine powder samples (usually <100 mg) and some bone samples were extracted as described (15), and mtDNA was amplified using a two-step PCR protocol (12). In each PCR, one or two blocking primers, designed to anneal to the anatomically modern contaminant sequences (Cambridge Reference Sequence haplotype) and prevent their amplification (27), were added.…”
Section: Methodsmentioning
confidence: 99%
“…In humans, KITLG is not associated with cancer risk, although rare germline KIT mutations have been associated with familial gastrointestinal stromal tumours (GIST), a type of gastrointestinal sarcoma [44]. Interestingly, there is precedent for the role of MC1R as a modifier of disease, as germline MC1R variants in humans affect pigmentation [45,46] and seemingly function as genomic modifiers for several human diseases [47][48][49][50][51], in one study conferring risk for BRAF-mutant melanoma [52].…”
Section: Germline and Cancer Riskmentioning
confidence: 99%
“…Between 2007 and 2009, by amplifying small nuclear regions encompassing functional variants, researchers found that some Neanderthals were probably red-haired and pale skinned [19], they had bitter taste perception ability [20] and presented the ABO blood type O [21]. In addition, having the same functional variants as modern humans in the FOXP2-a gene that when mutated generates a speech and language impediment-suggested that Neanderthals might have been able to communicate with similar language capabilities to ours, or at least they had the genetic basis to do so [22].…”
Section: The First Nuclear Dna Sequencesmentioning
confidence: 99%